Factors associated with the initiation of daily oral pre-exposure prophylaxis among adolescent girls and young women: findings from the Namibia DREAMS program - Moyo, Enos; Melese, Endalkachew; Mangwana, Hadrian; Takawira, Simon; Indongo, Rosalia; Harases, Bernadette; Moyo, Perseverance; Peresu, Ernest; Robert, Kopano; Dzinamarira, Tafadzwa (Frontiers in Public Health, 2025)
BackgroundAdolescent girls and young women (AGYW) aged 15–24 years in sub-Saharan Africa continue to face a significant risk of HIV acquisition. Oral pre-exposure prophylaxis (PrEP) can reduce the likelihood of HIV acquisition by more than 90% when adherence is optimal. The Determined, Resilient, Empowered, AIDS-Free, Mentored, and Safe (DREAMS) program, funded by PEPFAR/USAID and implemented by the Project HOPE Namibia (PHN)-led consortium, provided services in the Khomas, Oshikoto, Zambezi, and Oshana regions. The DREAMS program addresses factors that increase HIV vulnerability among AGYW. The objective of this secondary analysis of DREAMS program data is to assess the rate of daily oral PrEP initiation among AGYW aged 15–24, as well as the participants’ characteristics and HIV risk factors associated with PrEP initiation.MethodsThe program’s target populations for PrEP included AGYW aged 15–24 years, who were at substantial risk for HIV, tested HIV-negative, and resided in the regions where the PHN-led consortium was implementing the DREAMS program. Site-level personnel utilized the District Health Information Software 2 (DHIS2) Android Application for regular data collection. Data from 2018 to 2024 were analyzed using IBM Statistical Package for Social Sciences (SPSS) version 29. Data analysis employed Chi-squared tests and binomial and multivariate logistic regression.ResultsAmong the 29,828 AGYW eligible for PrEP, 24,182 (81.1%) were newly initiated on PrEP. AGYW from Windhoek and Oshakati, those enrolled between 2018 and 2023, those with 1–2 biological children, and those who perceived themselves at risk of HIV were more likely to initiate PrEP. In contrast, participants from Omuthiya and Tsumeb, those unaware of their partners’ HIV status, those with HIV-positive partners during pregnancy or breastfeeding, those with recent or recurrent sexually transmitted infections, those engaging in sexual activity while under the influence of alcohol or drugs, and those with multiple or concurrent sexual partners were less likely to initiate PrEP.ConclusionThe findings highlight the need for improved HIV education in smaller urban and rural communities to reduce stigma and discrimination against individuals taking PrEP. Additionally, enhancing HIV education to increase risk perception among AGYW at substantial risk for HIV is essential.